Moderate or greater daily coffee consumption is associated with lower incidence of metabolic syndrome in Taiwanese militaries: results from the CHIEF cohort study - Tsai, Kun-Zhe; Huang, Wei-Chun; Sui, Xuemei; Lavie, Carl J.; Lin, Gen-Min (Frontiers in Nutrition, 2023)
Daily moderate coffee intake was found with a lower risk of specific metabolic abnormalities, e.g., hypertension and hyperglycemia, while the association of coffee intake and incident metabolic syndrome (MetS) has not been clarified in prior studies, particularly in young adults.A total of 2,890 military personnel, aged 18-39 years, free of MetS were followed for incident MetS from baseline ( 2014) until the end of 2020 in Taiwan. Daily coffee amount consumed was grouped to those ≥3 cups or 600 mL (moderate or more amount) and those without. Incidence of MetS was identified in annual health examinations. MetS was diagnosed on the basis of the guideline of the International Diabetes Federation. Multivariable Cox regression model with adjustments for sex, age, body mass index, physical activity and substance use status at baseline was performed to determine the association.At baseline, there were 145 subjects with daily coffee intake ≥3 cups or 600 mL (5.0%) in the overall cohort. During a mean follow-up of 6.0 years, 673 incident MetS (23.3%) were found. As compared to those consuming less coffee or none, those consuming daily coffee ≥3 cups had a lower risk of MetS [hazard ratio (HR): 0.69 (95% confidence interval: 0.48, 0.99)].This study suggests that adhering to the guideline recommended moderate or greater daily coffee consumption for promoting health, may confer advantages in preventing the development of MetS among young adults.